Intellectual Property Protection Mechanisms and the Characteristics of Founding Teams - Sara Amoroso; Albert N. Link (European Commission, Joint Research Centre (JRC), 2019)
Intellectual property protection mechanisms (IPPMs) are critical to fostering innovation and their relevance has grown enormously with the increased trade in goods and services involving intellectual property. Scholars have investigated what factors facilitate or hinder the use of such IP protection strategies, identifying country, sector, and firm characteristics. However, the extant literature has overlooked the role of founding team characteristics on the choice of IPPMs. Using data from a large sample of European small and young entrepreneurial firms, we show that controlling for size, R&D intensity, and other firms and market effects, the founding team characteristics such as gender and education greatly influence the choice of IPPMs.
Keywords: M13; L26; O34; 330; IP choice; patents; appropriability; entrepreneurship; knowledge intensive firms; gender; AEGIS survey